On the Exploration of ‘The Id’ to Apprehend the Motives of the Murders Committed by Raskólnikov in Dostoevsky’s Crime and Punishment Novel - Lindawati, Ni Putu Fatmaha; Netra, I Made (Journal of A Sustainable Global South; Vol 3 No 1 (2019): February 2019DO - 10.24843/jsgs.2019.v03.i01.p05, 2019)
The objectives of this study are to explore the influence Raskólnikov’s Id on his motive murdering Alyona Ivanovna and her sister, Lizaveta; altogether to apprehend his motivations on committing the murders. The data in this study were collected from a novel entitled Crime and Punishment, written by a Russian author, Fyodor Dostoevsky. For collecting the data, this study used observation method and note taking technique; while to analyse the data, it used qualitative method as the data were in the form of texts. The theory used for analysing the data was the psychoanalysis theory proposed by Freud, which focused more on the Id and the concept of instincts. As the result, Raskólnikov’s Id was found to have a significant influence on his motives of committing the murders as his instinct persistently tried to up hold his pride as a man while he was crushed by poverty. His main motive on murdering Alyona Ivanovna was to avoid his pride being hurt as he found out that his family was suffering because of him. Meanwhile, his motive on murdering Lizaveta was purely come from his fear of failing to fulfil his first objective. Index Terms — the Id, motives, novel.